Pendampingan Pembuatan Karya Seni Berupa Kolase, Montase dan Mozaik pada Anak Kelas Tinggi Pendidikan Dasar - Sri Enggar Kencana Dewi; Resti Septikasari; Sulistyowati Sulistyowati (Jurnal Indonesia Mengabdi, 2020)
Arts, Culture and Craft subjects or often abbreviated as SBdP are subjects that exist in various educational institutions, especially in elementary schools. In the 2013 curriculum at this time in elementary schools the SBdP subject was included in thematic learning. So that those who teach this SBdP subject are class teachers whose backgrounds are various kinds of scientific experts. Most of the art lessons carried out in schools are only drawing. Whereas in this art, there are varied materials, one of which is the art of sticking, which includes collage, montage and mosaics. The methods used are lectures, questions and answers, demonstrations and discussions as well as direct mentoring. We are going to teach higher education elementary students about the art of sticking, namely collage, montage and mosaics. The result of this assistance is that it can increase children's creativity by utilizing existing materials into good work, can increase children's accuracy in doing something, and can practice crafts and patience in order to get the best work results.